2011
DOI: 10.4236/wet.2011.23023
|View full text |Cite
|
Sign up to set email alerts
|

Uniticket: A Third Party Universal E-Ticket System Based on Mobile Phone

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The ticket system discussed in this study is the latter type of scheme. Generally, four participants are involved in the e-ticketing system: an issuer, user, collector and third-party provider [17,19,20]. An issuer creates and issues a ticket with specified contents.…”
Section: E-ticketing Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…The ticket system discussed in this study is the latter type of scheme. Generally, four participants are involved in the e-ticketing system: an issuer, user, collector and third-party provider [17,19,20]. An issuer creates and issues a ticket with specified contents.…”
Section: E-ticketing Schemesmentioning
confidence: 99%
“…The third party may be the provider of the trading platform or may only be responsible for authenticating the transactions. Hu et al [19] proposed a universal e-ticket system, called Uniticket, which integrates all kinds of ticketing into one system. The Uniticket system has a trusted third-party platform and interfaces with personal and enterprise user ends.…”
Section: E-ticketing Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…This research focuses on the second sort of scheme, the ticket system. Issuer, user, collector, and a third-party supplier [ 4 , 6 , 7 ] are the usual players in an e-ticketing system. The contents of a ticket are determined by the issuer, who then makes and distributes the ticket to the buyer.…”
Section: Preliminarymentioning
confidence: 99%
“…The third party could be the platform’s host or it could just be in charge of verifying trades. Hu et al [ 6 ] suggested Uni-ticket, a unified electronic ticketing platform that supports several ticketing formats. The Uni-ticket system connects with both individual and corporate user ends, and it is built on a reliable third-party platform.…”
Section: Preliminarymentioning
confidence: 99%